Hubungan Derajat Perlemakan Hati Non Alkoholik Menggunakan Pemeriksaan Indeks Hepatorenal Software Image J Pada Ultrasonografi Dengan Peningkatan Kadar Serum Glutamik Pyruvik Transminase Di Rsup Dr. Hasan Sadikin Bandung - Faisal Reza; Redo Widhio Mahatvavirya (PRIMER (Prima Medical Journal), 2023)
Hepatorenal index sonography supported by ImageJ computer software program is one of the ultrasound parameters based on quantitative analysis to address the limitations of ultrasound in the diagnosis and determine the degree of non-alcoholic fatty liver. The degree of non-alcoholic fatty liver is divided into mild, moderate and severe. Increased ALT levels have a close relationship and a predictor of non-alcoholic fatty liver. Increased levels of ALT can influence the degrees of non alcoholic fatty liver. This research aim to determine the relationship between the degree of non alcoholic fatty liver using hepatorenal index J software image on the ultrasound and elevated ALT level in Dr. Hasan Sadikin General Hospital Bandung. This research is an analytic observational study with cross sectional design and concecutive admission sampling to determine the relationship between degree of non alcoholic fatty liver using hepatorenal index J software image on the ultrasound and elevated ALT level Dr. Hasan Sadikin General Hospital from January until March 2017. There are 39 study subjects consisted 22 women and 17 men, the youngest is 29 years old and the oldest is 69 years old. Results of statistical test Chi Square test at the 95% confidence level indicates that the mild non-alcoholic fatty liver mostly revealed on patients with increased ALT levels at the highest limit (100%), moderate non-alcoholic fatty liver mostly found in patients with high ALT levels (63.6%) and in severe non-alcoholic fatty liver can be found in very hight elevated ALT level (50.0%), with p <0.001 (value p ≤ 0,05). There is a significant relationship between degree of non-alcoholic fatty liver using hepatorenal index J software image on the ultrasound and elevated ALT level in Dr. Hasan Sadikin General Hospital Bandung. We conclude that there is a significant relationship between degree of non-alcoholic fatty liver using hepatorenal index J software image on the ultrasound and elevated ALT level in Dr. Hasan Sadikin General Hospital Bandung